Critical Analysis of Principal Supervision on Teachers' Professional Competence in the Learning Process at State Kindergartens in Banjarnegara Regency - Mudianto, Agus; Suyitno, Y.; Aryani, Ine Kusuma (Proceedings Series on Social Sciences & Humanities, 2025)
This study is about the analysis of Principal supervision, State Kindergartens in Banjarnegara Regency, aims to find out how the professional competence of kindergarten teachers is in the learning process, the supervision strategy of the Kindergarten Principal, the Implementation. of professional competence of kindergarten teachers in the learning process in kindergarten classes, the learning outcomes of students in kindergarten in the learning process. This research method is descriptive qualitative, namely a research method that uses data in the form of written or spoken language from people and actors that can be observed according to events and situations and conditions that occur, the research subjects are Kindergarten Principals and Kindergarten Teachers, data collection techniques are observation, interviews and documentation. Data analysis techniques are data collection, reduction, presentation, and collection. Research results: 1) The professional competence of Kindergarten teachers in the learning process in Kindergarten classes has improved better after periodic supervision by Kindergarten Principals; 2) The Kindergarten Principal's supervision strategy in improving the professional competence of teachers in the learning process, namely Planning a supervision program, Implementation of supervision carried out in the four Pembina State Kindergartens in order to improve the professional competence of teachers in the learning process: class visits, observations during the learning process, individual and comprehensive discussions about the results of supervision, Evaluation of supervision activities that have been carried out in the form of guidance and direction both individually and comprehensively, 3) Implementation of the professional competence of Kindergarten Teachers can be carried out well, 4) Student learning outcomes in Kindergartens in the learning process have increased.